Utilization of jeruju leaves extract (Acanthus ilicifolius) as a raw anti-acne cream - Nusaibah, Nusaibah; Pangestika, Widya; Herry, Herry (Sangia Research Media and Publishing, 2021)
Jeruju (Acanthus ilicifolius) is abundant in mangrove ecosystems in Indonesia and has high antibacterial, antioxidant and anti-inflammatory properties. In addition, the many uses of hazardous chemicals in anti-acne creams are the reason for the need of alternative natural ingredients for making anti-acne creams. So that in this study the use of jeruju leaf extract was added as an active ingredient of anti-acne cream. This research method was carried out by extracting the leaves of jeruju using ethanol solvent then made anti acne cream with extract concentrations of 1%, 5%, 10%, 15%. After that, sensory testing, TPC, antioxidant activity and antibacterial activity against acne-causing bacteria, namely Propionibacterium acne were carried out. The results of the antibacterial activity test of the four concentrations against P.acne produced inhibition zones with a range of values, namely 10.35-12.72 mm.. In testing the antioxidant activity, the best results were obtained at a concentration of 15% extract with an IC50 value of 98.80 ppm. From these results it can be concluded that jeruju is proven to inhibit P.acne bacteria, so that it has the potential to be used as an active ingredient in making anti-acne creams. Suggestions that can be given for further research are to make jeruju extract into a form that is more acceptable to consumers in terms of odor and color without reducing its content.